Simulation Analyses of High‐Efficiency Monolithic Solar Cells with Reduced Shunt and Lateral Forward Bias Current. Issue 18 (24th June 2022) - Xue, Shujian; Goryll, Michael; Bowden, Stuart G.
Abstract : Larger solar cells are preferred for higher power output. However, they produce higher current and lead to higher ohmic loss. This loss has prompted manufacturers to laser cut cells into halved cells, resulting in lower current, higher voltage string‐cells. While these techniques reduce ohmic loss, they introduce cutting‐edge recombination. The monolithic solar cell resembles halved cell but without requiring cutting the original cell into strings of cells which saved the cutting‐edge recombination loss. However, we observed that the interconnection of base regions of the string‐cells on the same wafer leads to problems such as lateral forward bias current, resulting in severe degradation of the fill factor (FF) and open‐circuit voltage ( V OC ). Solutions to these issues are proposed including depassivated surfaces between string‐cells, optimized spacing between the string‐cells, lowered base doping density, thinner wafers, and shading regions between the string‐cells. According to simulation results, these methods could increase the efficiency of the monolithic cell to very close to the baseline cell. With the consideration of the reduced shading, ohmic loss, and module blank areas on the cell‐to‐module process, the efficiency of a module with monolithic cells could exceed that of a module with baseline cells or a module of halved/shingling cells. Abstract : Herein, an innovative structure known as monolithic cell is presented. By making multiple string‐cells on the same wafer and interconnected in series, the output current is greatly reduced and thus the grid ohmic loss would reduce with it. With ultrathin and lowly doped wafers, the efficiency of monolithic cell modules can exceed baseline cell modules.